2011
DOI: 10.1097/rli.0b013e3182183a95
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive In Vivo Assessment of Renal Tissue Elasticity During Graded Renal Ischemia Using MR Elastography

Abstract: Objectives Magnetic Resonance Elastography (MRE) allows noninvasive assessment of tissue stiffness in vivo. Renal arterial stenosis (RAS), a narrowing of the renal artery, promotes irreversible tissue fibrosis that threatens kidney viability and may elevate tissue stiffness. However, kidney stiffness may also be affected by hemodynamic factors. This study tested the hypothesis that renal blood flow (RBF) is an important determinant of renal stiffness as measured by MRE. Material and Methods In six anesthetiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 33 publications
(40 reference statements)
7
107
1
2
Order By: Relevance
“…This led us to postulate whether reduced renal perfusion in HRS would translate to reduced renal stiffness on MRE. This hypothesis is supported by two animal studies that suggest that renal perfusion is an important determinant of renal stiffness [10,15]. Gennisson et al investigated the influence of blood pressure on renal stiffness using ultrasound elastography [15].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This led us to postulate whether reduced renal perfusion in HRS would translate to reduced renal stiffness on MRE. This hypothesis is supported by two animal studies that suggest that renal perfusion is an important determinant of renal stiffness [10,15]. Gennisson et al investigated the influence of blood pressure on renal stiffness using ultrasound elastography [15].…”
Section: Discussionmentioning
confidence: 93%
“…These properties of living tissues, including between physiologic and pathologic states, vary over a wider dynamic range on MRE compared with conventional imaging modalities such as ultrasound, computed tomography or magnetic resonance imaging (MRI). Early studies have suggested that MRE is sensitive to pathophysiologic changes such as renal fibrosis and renal hypoperfusion [9][10][11][12]. To our knowledge, the clinical feasibility of MRE for detecting HRS in patients with cirrhosis has not previously been reported.…”
Section: Introductionmentioning
confidence: 96%
“…Based on the assumption that excessive extracellular matrix deposition in fibrotic tissues increases their stiffness, MREderived stiffness has been used as an index of fibrosis. The feasibility of using MRE in the kidney has been demonstrated in transplant patients (43) and in swine renal artery stenosis (44,45). Interestingly, studies utilizing graded renal ischemia demonstrated that hemodynamic modulation of renal cortical stiffness hampers discrimination of fibrotic from nonfibrotic kidneys (44).…”
Section: Emerging Methods Elastographymentioning
confidence: 99%
“…The feasibility of using MRE in the kidney has been demonstrated in transplant patients (43) and in swine renal artery stenosis (44,45). Interestingly, studies utilizing graded renal ischemia demonstrated that hemodynamic modulation of renal cortical stiffness hampers discrimination of fibrotic from nonfibrotic kidneys (44). However, MRE is capable of detecting fibrosis in the intrinsically hypoperfused medulla (45), which is less dependent on perfusion pressure.…”
Section: Emerging Methods Elastographymentioning
confidence: 99%
“…There have been many studies on the usefulness of ultrasound and magnetic resonance elastography for assessment of hepatic fibrosis in patients with chronic liver disease. 8,[13][14][15][16][17][18] Recent clinical studies used noninvasive diagnostic tools (eg, acoustic radiation force impulse imaging and transient elastography) for transplanted kidney monitoring. [19][20][21] These studies showed the clinical feasibility of ultrasound elastography for kidney evaluation.…”
mentioning
confidence: 99%